Harmonisasi Nilai-Nilai Islam dan Kearifan Lokal: Perspektif Filosofis tentang Salam Adat Dayak Menurut Al-Qur'an - Mahfuzh, Taufik Warman; Wardani, Wardani (Pascasarjana UIN ANTASARI Banjarmasin, 2024)
This research analyzes the philosophical values in Salam Tradisi Dayak and their relevance to the goals of Islamic education based on the Qur'anic perspective. This research uses content analysis method with descriptive-qualitative approach. Data were collected through a review of relevant literature and analyzed systematically using data reduction, categorization, and in-depth interpretation techniques. This research found that Salam Tradisi Dayak include three main concepts: Adil Ka'talino (justice), Bacuramin Ka'saruga (reflection of goodness), and Basengat Ka'jubata (awareness of God ' s existence). These three concepts are in line with the goals of Islamic education which include aspects of faith, worship, and morals. The study concludes that Salam Tradisi Dayak can be an important foundation for building individual religious and moral awareness, as well as creating harmony between religious values and local wisdom. The implication of this study is the importance of preserving Salam Tradisi Dayak as a form of local wisdom that can be integrated into Islamic education to build moral and religious awareness, and create harmony between local culture and Islamic values. This integration is also expected to strengthen the cultural and religious identity of the people of Kalimantan in the context of modern life.